Social comparison and self esteem in indoor rock climbing - Tay, Vincent Yan Chiang (Nanyang Technological University, 2020)
Background: Self-esteem and social comparison are qualities that are observed in indoor rock climbing, much like any other competitive sport. Indoor rock climbing competitions are held on a yearly basis in Singapore and many athletes partake in them. Objective: The objective of this study was to investigate the relationship between the level of self-esteem and type of social comparison one does as defined by their competitive category and years of climbing experience. Design: Quantitative cross-sectional study. Methods: 206 participants completed a questionnaire on Sport State Self-Esteem, Upward Social Comparison and Downward Social Comparison. Results: Open category climbers (p = .003) had a statistically significantly higher Sport State Self-Esteem than Novice category climbers. Open category climbers (p = .031) had a statistically significantly lower Upward Social Comparison than Intermediate and Novice category climbers. Open category climbers (p = .025) had a statistically significantly lower Downward Social Comparison than Intermediate and Novice category climbers. Between Climbing Experience and USC, there was a significant weak negative correlation, rs = -.262, p < .01. Conclusions: “Beta” is a jargon in climbing that is an important component in indoor rock climbing. The information from beta obtained from others is what drives the notion of Upward or Downward social comparison. Sport State Self-Esteem is then a consequence that fluctuates depending on the social comparison one does in the competitive nature of indoor rock climbing. Keywords: Indoor Rock Climbing, Sport State Self-Esteem, Social Comparison